The Influence of Financial Literacy and Lifestyle - Rustama, Hendra (Journal of Economics and Public Health, 2025)
Individual financial management behavior is a crucial factor in determining economic well-being, especially in today’s era of high consumerism. Low financial literacy and unhealthy lifestyles are often the primary causes of poor personal financial management. This study aims to determine the influence of financial literacy and lifestyle on financial behavior among respondents. A quantitative method with a descriptive correlational approach was used. The sample consisted of 100 respondents selected through purposive sampling. Data was collected using a questionnaire, then data analysis was carried out using percentages in univariate, partial tests and simultaneous tests. Descriptive analysis showed that the majority of respondents had good financial literacy (84%), a good lifestyle (78%), and positive financial behavior (83%). Multiple linear regression analysis indicated that financial literacy had a significant effect on financial behavior (p = 0.000; β = 0.725), and lifestyle also had a significant effect (p = 0.002; β = 0.202). Simultaneous testing (ANOVA) revealed that financial literacy and lifestyle together significantly influenced financial behavior (p = 0.000; F = 141.193). It can be concluded that better financial literacy and a more positive lifestyle are associated with better individual financial behavior. These findings highlight the importance of financial education and lifestyle control in supporting healthy financial management.